Introduction of green-fluorescent protein (GFP) gene in Musa acuminata cv. mas (AA). - Kadir M. A. (Malaysian Society of Plant Physiology, 2021)
In order to introduce genes with agronomic value into banana, genetic transformation protocols have to be optimized. A PDS-1000/Helium delivery system was used to introduce the plasmid vector pGEM, which carries the GFP gene driven by the Ubi 1 promoter into the scalp and embryogenic cell suspension of banana cv. Mas. Three (3) bombardment variables that affect transformation efficiency were examined which were the gold microcarrier size of 1.0 I-lm, rupture disk pressure of 900, 1100 and 1350 psi and the target distance of 6, 9 and 12 cm. Transient GFP gene expression was assayed I to 14 days postbombardment which revealed that the highest number of transient transformants of scalp was obtained with the helium pressure of 1100 and 1350 psi along with a target distance of 9 cm and the highest number of transient transformants of embryogenic cell suspension was attained at 900 psi helium pressure with a target distance of 6 cm.